Bothropoides pauloensis venom effects on isolated perfused kidney and cultured renal tubular epithelial cells - Marinho, Aline Diogo; Morais, Isabel Cristina Oliveira de; Lima, Dânya Bandeira; Jorge, Antônio Rafael Coelho; Jorge, Roberta Jeane Bezerra; Menezes, Róseo Paula Pessoa Bezerra de; Mello, Clarissa Perdigão; Pereira, Gustavo José da Silva; Silveira, João Alison de Moraes; Toyama, Marcos Hikari [UNESP]; Orzáez, Mar; Martins, Alice Maria Costa; et al. (Elsevier B. V., 2015)
Snake envenomation (Bothrops genus) is common in tropical countries and acute kidney injury is one of the complications observed in Bothrops snakebite with relevant morbidity and mortality. Here, we showed that Bothropoides pauloensis venom (BpV) decreased cell viability (IC50 of 7.5 μg/mL). Flow cytometry with annexin V and propidium iodide showed that cell death occurred predominantly by apoptosis and late apoptosis, through caspases 3 and 7 activation, mitochondrial membrane potential collapse and ROS overproduction. BpV reduced perfusion pressure, renal vascular resistance, urinary flow, glomerular filtration rate, percentage of sodium, chloride or potassium tubular transportation. These findings demonstrated that BpV cytotoxicity on renal epithelial cells might be responsible for the nephrotoxicity observed in isolated kidney.
Keywords: Bothropoides pauloensis; Cell death; Renal effects